The square is zero, so you can just remove it (take the sqrt of both sides). Now solve by using quadratic formula.
a = 5
b = 6
c = 12
x = [ -b +/- sqrt(b^2 - 4ac) ] / 2a
x = [-6 +/- sqrt(6^2 - 4(5)(12)) ] / 2(5)
x = -3/5 +/- sqrt(36 - 240) / 10
x = -3/5 +/- sqrt(-204) / 10
x = -3/5 +/- 1/5 sqrt(-51)
x = -3/5 +/- 1/5 sqrt(51) i
So you have two imaginary roots
2006-10-25 13:51:20
·
answer #1
·
answered by Puzzling 7
·
0⤊
1⤋
The last squaring is irrelevant. The only way (...)^2 can be 0
is for (...) to be 0.
so solve
5z^2 + 6z + 12 = 0
The quadratic formula
z = (-b + or - sqrt(b^2 - 4ac))/2a
with a = 5, b = 6, c = 12
will give a negative value for
b^2 - 4ac,
which means you get complex roots.
Do it yourself, but I think you get
z = -0.6 + 0.2*sqrt(51)*i
or z = -0.6 - 0.2*sqrt(51)*i
2006-10-25 20:56:57
·
answer #2
·
answered by Hy 7
·
0⤊
0⤋
z=4
2006-10-25 20:47:21
·
answer #3
·
answered by Anonymous
·
0⤊
0⤋
Write it out like this:
(5z^2 + 6z + 12)(5z^2 + 6z + 12),
which extends to:
(5z^2)(5z^2 + 6z + 12) + (6z)(5z^2 + 6z + 12) + (12)(5z^2 + 6z + 12)
2006-10-25 20:52:35
·
answer #4
·
answered by topher8128 2
·
0⤊
0⤋
(5z^2 + 6z +12)^2 = 0 this is really a lot simpler than it looks. just take the sqrt of both sides & get:
(5z^2 + 6z +12) = 0
z=(-6+/-sqrt(36-240))/10
z=(-6+/-sqrt(-204))/10=-3/5+/-1/5sqrt(-51)
z=-.6-.2sqrt(51) i
z=-.6+.2sqrt(51) i
2006-10-25 20:51:42
·
answer #5
·
answered by yupchagee 7
·
0⤊
0⤋
quadratic formula
z=-6/10+-[sqrt(36-240)]/10
= -3/5 +-[sqrt(204]i/10
2006-10-25 20:58:18
·
answer #6
·
answered by rwbblb46 4
·
0⤊
0⤋
the only solutions are complex (not real numbers)
(3 + or - i*sqrt(51)) / 5
2006-10-25 20:52:16
·
answer #7
·
answered by Marcella S 5
·
0⤊
0⤋
factor the quadratic
2006-10-25 20:46:40
·
answer #8
·
answered by Gemma darling 2
·
0⤊
0⤋
ok i dont know
2006-10-25 20:45:58
·
answer #9
·
answered by sue16683@verizon.net 2
·
0⤊
1⤋